Secular Trends in Infection-Related Mortality after Kidney Transplantation - Kinnunen, Susanna (Clin J Am Soc Nephrol, 2018)
BACKGROUND AND OBJECTIVES: Infections are the most common noncardiovascular causes of death after kidney transplantation. We analyzed the current infection-related mortality among kidney transplant recipients in a nationwide cohort in Finland. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Altogether, 3249 adult recipients of a first kidney transplant from 1990 to 2012 were included. Infectious causes of death were analyzed, and the mortality rates for infections were compared between two eras (1990–1999 and 2000–2012). Risk factors for infectious deaths were analyzed with Cox regression and competing risk analyses. RESULTS: Altogether, 953 patients (29%) died during the follow-up, with 204 infection-related deaths. Mortality rate (per 1000 patient-years) due to infections was lower in the more recent cohort (4.6; 95% confidence interval, 3.5 to 6.1) compared with the older cohort (9.1; 95% confidence interval, 7.6 to 10.7); the incidence rate ratio of infectious mortality was 0.51 (95% confidence interval, 0.30 to 0.68). The main causes of infectious deaths were common bacterial infections: septicemia in 38% and pulmonary infections in 45%. Viral and fungal infections caused only 2% and 3% of infectious deaths, respectively (such as individual patients with Cytomegalovirus pneumonia, Herpes simplex virus meningoencephalitis, Varicella zoster virus encephalitis, and Pneumocystis jirovecii infection). Similarly, opportunistic bacterial infections rarely caused death; only one death was caused by Listeria monocytogenes, and two were caused by Mycobacterium tuberculosis. Only 23 (11%) of infection-related deaths occurred during the first post-transplant year. Older recipient age, higher plasma creatinine concentration at the end of the first post-transplant year, diabetes as a cause of ESKD, longer pretransplant dialysis duration, acute rejection, low albumin level, and earlier era of transplantation were associated with increased risk of infectious death in multivariable analysis. CONCLUSIONS: The risk of death due to infectious causes after kidney transplantation in Finland dropped by one half since the 1990s. Common bacterial infections remained the most frequent cause of infection-related mortality, whereas opportunistic viral, fungal, or unconventional bacterial infections rarely caused deaths after kidney transplantation.